1975
DOI: 10.1007/bf01732005
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive character of liver glucokinase

Abstract: 1. Glucokinase is one of four glucose phosphorylating enzymes present in rat liver. Its distinctive features are a high K-m for glucose (high-K-m isozyme) and a rather narrow substrate specificity. In contrast, the other three enzymes, collectively called hexokinases or low-K-m isozymes, exhibit low K-m values for glucose and a wider substrate specificity. 2. Glucokinase is present in the liver os mammals (with some exceptions), amphibians and lower reptiles; It is absent from higher reptiles and birds. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…Glucokinase (EC 2.7.1.2) is the principle glucose-phosphorylating enzyme in the liver parenchymal cells of many species and has properties that equip it to fulfil a unique role in the regulation of hepatic glucose utilization [1,2]. Most studies on the enzyme and its regulation have used the rat.…”
mentioning
confidence: 99%
“…Glucokinase (EC 2.7.1.2) is the principle glucose-phosphorylating enzyme in the liver parenchymal cells of many species and has properties that equip it to fulfil a unique role in the regulation of hepatic glucose utilization [1,2]. Most studies on the enzyme and its regulation have used the rat.…”
mentioning
confidence: 99%
“…The enzyme solubilized from the Golgi preparation did not cross-react with an antiserum prepared against cytoplasmic glucokinase and showed different affinity from the cytoplasmic enzyme for concanavalin A. In the diabetic and neonatal rat livers the activities of Golgi glucokinase were similar to those found in the adult animal, which is different from the cytoplasmic enzyme, which decreases to very low activity in the diabetic rat (see Niemeyer et al, 1975, for a review) and only normally first appears in the developing rat around the time of weaning from 16 days of age onwards (Walker & Holland, 1965). The latter observations suggest that the two glucokinase enzymes do not have the same metabolic role in the liver cell, even though they both have comparatively high Km values for glucose.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the well-established cytoplasmic glucokinase (EC 2.7.1.2) (Walker, 1966;Niemeyer et al, 1975), some glucokinase activity possessing different kinetic characteristics is associated with microsomal fractions prepared from rat liver (Berthillier et al, 1970;Berthillier & Got, 1972). Most of this activity could be recovered in a microsomal subfraction containing Golgi material prepared by zonal centrifugation (Berthillier et al, 1973).…”
mentioning
confidence: 99%
“…From the work of several groups it is known that hexokinase D, 'glucokinase' (ATP: D-glucose 6-phosphotransferase, EC 2.7.1.2), is affected markedly in the whole liver by dietary and hormonal manipulations [for references see reviews by Niemeyer et al (1975) and by Weinhouse (1976)]. The variations in hexokinase D activities are the result of changes in the amount of enzyme protein, as recognized by immunotitration (Clark-Turri et al, 1974), and are related to the concentrations of the specific RNA (Spence, 1983).…”
mentioning
confidence: 99%
“…Most workers have only measured the combined activity of hexokinases A, B and C by using the spectrophotometric assay method of Viniuela et al (1963), a procedure that has several limitations (Niemeyer & Ureta, 1972;Reyes & Cardenas, 1984). Although there is general agreement on the constancy of total high-affinity hexokinase activity in liver after dietary and hormonal treatments [for reviews see Niemeyer et al (1975) and Weinhouse (1976)], some authors have described variations in certain conditions. Thus Machiya & Hoyosa (1969) reported a decrease in hexokinase B activity in liver from diabetic rats; Pilkis (1970) reported an increase in the total activity of high-affinity hexokinases in the liver of hypophysectomized rats treated with thyroxine; and Wakelam et al (1979) similarly observed an increase in the liver of neonatal rats treated with triiodothyronine.…”
mentioning
confidence: 99%